Nutritional value and development prospect of edible dock - WANG Xiao-jie; LIU Kang; ZHANG Li; ZHENG Ming-ming; ZHOU Yi-bin (Shipin yu jixie)
To investigate the physicochemical properties of edible dock, promote its processing and develop the related products, the safety, advantages as a new food raw material, nutritional components, health efficacy and application status of the edible dock were reviewed, and the prospects for the development of edible dock products were also presented.